Pengaruh Strategi Pemasaran dan Pelayanan terhadap Kepuasan Mahasiswa pada STIE Mahaputra Riau - Firmansyah Firmansyah (Jurnal Samudra Ekonomi dan Bisnis, 2019)
The purpose of this study is to determine the effect of marketing strategies on student satisfaction at STIE Mahaputra Riau, to determine the effect of service on student satisfaction at STIE Mahaputra Riau. The results of this study are that marketing strategies affect student satisfaction at STIE Mahaputra Riau, service influences student satisfaction at STIE Mahaputra Riau, and the coefficient of determination is 92,% which means that student satisfaction can be explained by 92% marketing and service strategies while the rest is influenced by other factor.